BAISIC STAGES, PRINCIPLES AND METHODS OF MULTI-PARADIGMAL METHODOLOGY IN LINGUISTICS, TRANSLATOLOGY AND LITERARY CRITICISM - Terekhova, Svitlana (Collection of scientific papers «ΛΌГOΣ», 2025)
In modern philological fields of science more and more attention of scholars is paid to multi-paradigmal methodology of conducting their research. Its topicality is determined by complex approach, provided in framework of multi-paradigmal analysis, that permits to observe the object of the research systematically, in complex, from different aspects.